Iron carbide nanoparticles supported on an N-doped carbon porous framework as a bifunctional material for electrocatalytic oxygen reduction and supercapacitors. Issue 48 (30th November 2022) - Han, Zengyu; Cai, Wenfang; Zhao, Shifeng; Zhao, Yi; Bai, Jirui; Chen, Qingyun; Wang, Yunhai
Abstract : Fe3 C/PNCF is prepared as a bifunctional material for a low half-wave potential of 0.84 V toward electrocatalytic ORR and a high specific capacitance of 385.3 F g −1 under 1 A g −1 . Abstract : Highly active and durable bifunctional materials are of pivotal importance for energy conversion and storage devices, yet a comprehensive understanding of their geometric and electronic influence on electrochemical activity is urgently needed. Fe–N–C materials with physical and chemical structural merits are considered as one of the promising candidates for efficient oxygen reduction reaction electrocatalysts and supercapacitor electrodes. Herein, Fe3 C nanoparticles supported on a porous N-doped carbon framework (denoted as Fe3 C/PNCF) were readily prepared by one-step chemical vapor deposition under the assistance of a NaCl salt template. The experiment results revealed that the as-synthesized Fe3 C/PNCF nanocomposites successfully displayed attractive electrocatalytic oxygen reduction reaction (ORR) activity comparable to that of the Pt/C catalyst ( E 1/2 of 0.84 V and 0.83 V, respectively), and a superior capacitance of 385.3 F g −1 under 1 A g −1 for a supercapacitor. It's proposed that the increased pyridinic and graphitic N coordination on the hydrophilic porous framework provides more electrochemical active surface area for the storage and transport of electrolyte ions. Additionally, an appropriate d-band center created by the optimized adsorption function endows Fe3 C/PNCF with excellent electrochemical properties. The results confirmed that the integration strategy of porous heterogeneous structure and accessible active sites balanced the complex relationship between geometry, electronic structure, and electrochemical activity. Our research provides a facile approach for fabricating multi-functional nanomaterials applicable in both ORR and supercapacitors in the future.